2019
DOI: 10.1037/edu0000319
|View full text |Cite
|
Sign up to set email alerts
|

The 2I/E model: Integrating temporal comparisons into the internal/external frame of reference model.

Abstract: The 2I/E model is an extension of Marsh’s (1986) classical internal/external frame of reference (I/E) model. Whereas the classical I/E model describes the formation of academic self-concept by the joint operation of social (external) and dimensional (internal) comparisons, the 2I/E model integrates temporal comparisons as an additional internal comparison process. In the 2I/E model, paths from achievement levels to self-concepts in the same subject are assumed to represent social comparisons, paths from achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(84 citation statements)
references
References 121 publications
6
77
0
1
Order By: Relevance
“…Another limitation is that the meta-analysis did not deal with temporal comparisons that might also affect self-concept. Wolff, Helm, Zimmermann, et al (2018), Wolff, Nagy, et al (2019), and Wolff, Helm, et al (2019), in experimental and field studies, analyzed the simultaneous effects of social, temporal, and dimensional comparisons on students’ academic self-concepts in various domains. In all studies, social, temporal, and dimensional comparisons showed significant effects on self-concept.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation is that the meta-analysis did not deal with temporal comparisons that might also affect self-concept. Wolff, Helm, Zimmermann, et al (2018), Wolff, Nagy, et al (2019), and Wolff, Helm, et al (2019), in experimental and field studies, analyzed the simultaneous effects of social, temporal, and dimensional comparisons on students’ academic self-concepts in various domains. In all studies, social, temporal, and dimensional comparisons showed significant effects on self-concept.…”
Section: Discussionmentioning
confidence: 99%
“…Recent extensions of comparison research that address the development of academic self-concepts dealt with three prominent comparison processes: social, temporal, and dimensional comparisons (Müller-Kalthoff et al, 2017; Wolff, Helm, Zimmermann, et al, 2018; Wolff, Nagy, et al, 2019). Social comparisons use others as interindividual standards in order to judge the self (Festinger, 1954; Gerber et al, 2018), whereas temporal comparisons use former achievements as intraindividual standards (Albert, 1977; Wilson & Ross, 2000), and dimensional comparisons use other domains as intraindividual standards (Möller & Köller, 2001a; Möller & Marsh, 2013).…”
mentioning
confidence: 99%
“…Prior theory suggests that dimensional, social, and temporal comparisons are primary contributors to the self-concept (Albert, 1977; Festinger, 1954; Möller & Marsh, 2013), but few studies have examined the simultaneous effects of all three standards. Initial research suggests that social comparisons are more strongly associated with (Wolff, Helm, et al, 2018, study 3; Wolff, Nagy, et al, 2018) and have a descriptively larger effect on self-evaluations (Wolff, Helm, et al, 2018, study 1) than dimensional and temporal comparisons. The present research provides the first evidence that social comparisons have a significantly larger effect on self-evaluations than dimensional and temporal comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being limited to only a few studies, emerging research examining three comparison sources is also consistent with the proposed primacy of social comparison. Specifically, longitudinal path-analytic studies of academic self-evaluations found large, medium, and small associations of self-evaluations with social, dimensional, and temporal comparison information, respectively (Wolff, Helm, et al, 2018, study 3; Wolff, Nagy, et al, 2018). Such data are impressive in their demonstration of comparison associations with self-evaluations in large samples (i.e., tens of thousands of students) and in externally valid conditions; however, the use of nonexperimental methods prevents causal conclusions.…”
Section: Multiple Comparison Sourcesmentioning
confidence: 99%
“…Furthermore, students can easily compare their own school grades in one subject with other students’ school grades in the same subject (social comparisons), with their own school grades in other subjects (dimensional comparisons), and with their own school grades in the same subject at previous points in time (temporal comparisons). These comparison processes have been conceptualized as an important mechanism of ASC formation (Möller et al, 2009, 2020; Wolff et al, 2019). The findings from between-network analyses have supported the domain specificity of ASC.…”
Section: Part 1: Within-network and Between-network Analyses On The Smentioning
confidence: 99%